Eubacterium limosum JCM6421T influences quercetin production from isorhamnetin and short-chain fatty acid production from various sugars - Tamura, Motoi; Nakagawa, Hiroyuki; Hirayama, Kazuhiro (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
Isorhamnetin (3′-methylquercetin) is one of the major metabolites of quercetin. We hypothesized that Eubacterium limosum JCM6421T transforms isorhamnetin back to quercetin and the type of sugar affects short-chain fatty acid production by E. limosum JCM6421T. Anaerobic broth (0.2 mL) containing this bacterium was added to the isorhamnetin solution and anaerobically incubated for 8 and 24 h. Additionally, E. limosum JCM6421T was anaerobically incubated with various 2 µL-sugar solutions for 24 h and short-chain fatty acid production by this bacterium was measured. Quercetin was produced by anaerobic incubation of isorhamnetin with E. limosum JCM6421T. Its production increased with an increase in incubation time from 8 to 24 h. Mannitol was the ideal sugar for butyric and acetic acid production by E. limosum JCM6421T among the investigated sugars. We discovered that E. limosum JCM6421T produces quercetin from isorhamnetin.